Elucidating the Structural Requirements of Novel Pazopanib Derivatives towards Tyrosine Kinase Inhibitory Activity through Classical Hansch and De-Novo Approach - Gupta, Nidhi; Soni, Love (Journal of Drug Delivery and Therapeutics, 2017)
Quantitative structure–activity relationship (QSAR) and Molecular modeling study have been performed on a series of novel Pazopanib derivatives by using the Mixed Hansch Fujita-Ban approach and employing AM1 calculations in docking study which give insight into the structural requirements of the derivatives towards inhibitory activity against VEGFR-2, PDGFR-α and c-kit tyrosine kinases enzymes. Evaluation of the predictive ability of the resulting models is carried out by using ‘Leave-one-out’ (LOO) method of cross validation. There is a remarkable agreement in the results of both the approaches. From the QSAR study it can be inferred that methyl substitution at 5th position of the terminal benzene ring and hydrophobicity play a key role in kinase inhibitory activity. Potential binding sites were elucidated by docking study. Docking simulations was performed through Molegro Virtual Docker (MVD) for lead optimization of compound as protein tyrosine kinase inhibitors.